Digital Archiving: Journey from Books to Analytical Informatics - Marie Scandone; Deborah Kernan (Issues in Science and Technology Librarianship)
It can be an enormous undertaking to obtain spectral information from a number of different analytical instruments, present it in a digital format and archive the data. Sadtler Research Laboratories has been producing quality spectral information for the analytical laboratory since 1947. The history is fascinating and the process is unusual. The journey that Sadtler Research Laboratories has taken to become Bio-Rad Laboratories, Informatics Division is a part of the history of the evolution of chemical information. Along the way, Bio-Rad changed their method of spectral data delivery but retained focus on the quality of the analytical information. This article examines the transition from print to digital media.